A Comparative Study for Various Morphological Characters between Diploid and Triploid Watermelon - Padhan, Abhilash; Kumar, T. Pradeep (International Journal of Economic Plants, 2022)
The present study was carried out during May–July, 2015 at the High-tech seed testing laboratory under the Department of Vegetable Science, Kerala Agriculture University, Trissur, India to differentiate between the normal diploid(2x) watermelon var. Sugar Baby with the yellow seedless triploid(3x) watermelon hybrid var. Swarna (KAU-CL-TETRA-1 × CL-5). In the present study chloroplast count and pollen grain study were undertaken as the morphological markers to carry out the experiment. The true leaf samples collected from 10 numbers of diploid(2x) var. Sugar Baby and 7 numbers of triploid (3x) var. Swarna(KAU-CL-TETRA-1 × CL-5) seedlings of watermelon were taken for the study whereas Binocular compound microscope (Olympus ICON-Tr Freedom) at 100x magnification was used for counting the number of chloroplasts present in the guard cell of stomata. Around 40 numbers of stomatal guard cells were taken into consideration for counting the average chloroplast number for each sample. The pollen grain was studied after staining with red safranin and observed under the compound microscope. The results obtained from the average chloroplast count of 10 samples of diploid (2x) watermelon var. Sugar Baby was 11.07 whereas the average chloroplast count of 7 samples of triploid (3x) watermelon hybrid var. Swarna (KAU-CL-TETRA-1 × CL-5) was 12.11. The pollen grain of triploid (3x) watermelon hybrid var. Swarna (KAU-CL-TETRA-1 × CL-5) was found to be not retained from red safranin stain color being sterile in nature whereas the fertile pollen of diploid (2x) watermelon var. Sugar Baby retained the stain color.